Risiko Paparan Sulfur Dioksida (SO2) pada Masyarakat yang Bermukim Disekitar PT. PLN (Persero) Sektor Tello Tahun 2014 - Wahyuddin, Putri Puspitasari; Susilawaty, Andi; Azriful, Azriful; Basri, Syahrul (HIGIENE: Jurnal Kesehatan Lingkungan, 2016)
Exhaust emissions released by power plants machines. There are various kinds of pollutants including SO2. This industry is located that is surrounded by residential areas so that the people around him at risk for exposure to Sulfur Dioxide (SO2). This research aimed to analyze the magnitude of the risk of exposure to SO2 on plant communities in the PT. PLN (Persero) Sektor Tello.This research used an observational method with the application of Environmental Health Risk Analysis (ARKL) approach. The sample of subjects of the this research were 104 respondents from four locations around the PT. PLN (Persero) Sector Tello. Samples object consisted of 4 points ambient air sampling. Results indicated that the average concentration of SO2 were 0,0445925 mg/m3.The average rate of intake based on age and sex were 10.98 m3day- and the average length of stay of respondents in research location which expressed as exposure duration was 21 years. Then, the average body weight was 58 kg. Likewise, it was found that the risks magnitude of exposure to SO2 that measured in the Risk Quotient (RQ) by the air sampling time was 4. 1252. Community surround the PT. PLN (Persero) Sector Tello has a high risk of exposure to SO2 exceeded the unite (RQ> 1) exposure have a low risk. It is suggested to those people to be alert and do periodic health checks and preventive efforts such as plant some vegetation to absorb the SO2 gas. Keywords : Risk Analysis, SO2, RQ (Risk Quotient)